Proceedings of IEEE International Electron Devices Meeting
DOI: 10.1109/iedm.1993.347259
|View full text |Cite
|
Sign up to set email alerts
|

0.15 μm CMOS with high reliability and performance

Abstract: 0 . 1 5~ CMOSFETs with high reliability and performance have been realized. The acceptable power supply voltage V, was estimated to be 1.9V. A reasonably short ring oscillator delay of 33ps was obtained for the 1.9V V, , maintaining an 0.4V threshold voltage. Anomalous surface state generation and Vm shift for the PMOS were observed, though the degradation was less severe than the nMOS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 3 publications
1
3
0
Order By: Relevance
“…This is similar to that discussed by [172]. Furthermore, it was said that Vc s tr = V Dstr will the worst case degradation condition for deep submicron devices having thin gate oxide in the gate direct tunneling regime [173,174,175].…”
Section: Core Transistorssupporting
confidence: 73%
“…This is similar to that discussed by [172]. Furthermore, it was said that Vc s tr = V Dstr will the worst case degradation condition for deep submicron devices having thin gate oxide in the gate direct tunneling regime [173,174,175].…”
Section: Core Transistorssupporting
confidence: 73%
“…In short channel NMOSFETs, lifetime at becomes shorter than that at [17]- [19]. This means that the CHE degradation caused by the hot electron injection alone becomes more severe than that caused by the hot carrier recombination.…”
Section: A Modeling Of Channel Hot Electron Lifetimementioning
confidence: 95%
“…On the other hand, it has been reported that worst case gate voltage condition changes from the traditional condition to the channel hot electron (CHE) condition at in short channel NMOSFETs [17]- [19]. Modeling of the CHE degradation is also needed.…”
Section: Introductionmentioning
confidence: 98%
“…16 Programming current (I g e ) measured in three different electron injection schemes for N-channel transistors fabricated by 0.14-μm technology (cell B). The drawn channel dimension (W/L) = 10/0.176 μm/μm and the tunnel-oxide thickness t ox = 8.1 nm.…”
mentioning
confidence: 99%